Fluoride and Liver Toxicity: A Zebrafish Model - MAMMADZADA, Laman; TORAMAN, Emine (International Conference on Applied Engineering and Natural Sciences, 2023)
Fluoride, which is exposed by living organisms through food and water intake, causes many health problems. The liver is one of the organs most affected by sodium fluoride (NaF) toxicity. Studies have shown that NaF causes many pathological and metabolic changes in the liver. Many studies have shown that exposure to high fluoride concentrations in drinking water elevates the levels of kidney and liver function enzymes in serum and causes severe histological changes in the liver and kidneys. However, there are limited studies on the liver toxicity of chronic fluoride intake in amounts close to daily usage doses. Therefore, in our study, the effect of chronic fluoride (NaF) exposure at low doses on zebrafish liver toxicity was investigated. Liver tissues of zebrafish exposed to NaF at doses of 1.5 ppm, 5 ppm, and 100 ppm for 6 weeks were used in the study. GSH and MDA levels were measured in these tissues. In addition, specific activities of GST and GR enzymes were determined. When the data obtained were examined, it was observed that while GST, GR, and GSH levels decreased, MDA levels increased, especially in the groups treated with 5 and 100 ppm NaF. This suggests that chronic exposure to fluoride, albeit at low doses, may be a risk factor.